2018
DOI: 10.1186/s13063-018-2535-5
|View full text |Cite
|
Sign up to set email alerts
|

Trial Forge Guidance 1: what is a Study Within A Trial (SWAT)?

Abstract: Randomised trials are a central component of all evidence-informed health care systems and the evidence coming from them helps to support health care users, health professionals and others to make more informed decisions about treatment. The evidence available to trialists to support decisions on design, conduct and reporting of randomised trials is, however, sparse. Trial Forge is an initiative that aims to increase the evidence base for trial decision-making and in doing so, to improve trial efficiency.One w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
232
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(232 citation statements)
references
References 10 publications
0
232
0
Order By: Relevance
“…Despite these problems and their effects on trial validity and costs, there is little rigorous quantitative research to support recruitment efforts. Embedding trials of different recruitment methods in trials (so called 'studies within a trial' or SWATs) is an effective way of testing methods [3] and is increasingly supported by funders [4], but a recent Cochrane review identified only 68 studies of this type [5].…”
Section: Resultsmentioning
confidence: 99%
“…Despite these problems and their effects on trial validity and costs, there is little rigorous quantitative research to support recruitment efforts. Embedding trials of different recruitment methods in trials (so called 'studies within a trial' or SWATs) is an effective way of testing methods [3] and is increasingly supported by funders [4], but a recent Cochrane review identified only 68 studies of this type [5].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this review could help improve the design and conduct of RCTs by helping researchers to identify and implements strategies to reduce research burden. Such strategies might be implemented and evaluated in a Study Within A Trial (SWAT) [42] and thereby add to the evidence base on recruitment and retention in trials [5,6]. Further, we need to explore other study designs that could reduce burden and improve external validity such as trials embedded in registries, cohorts, or routinely collected data [43] but also observational studies and use of routinely collected data.…”
Section: Toward Minimally Disruptive and Compassionate Clinical Researchmentioning
confidence: 99%
“…The primary outcome will be physical symptoms (PHQ-15) [20] at 52 weeks after randomisation. PHQ-15 comprises 15 physical symptoms, with each accorded 2,1 or 0 points based on how much they have bothered the patient over the last 4 weeks (bothered a lot, bothered a little, not at all).…”
Section: Assessments and Procedures 71 Primary Outcome Measurementioning
confidence: 99%